Advances in Conceptual Modeling. Recent Developments and New Directions ER 2011 Workshops FP-UML, MoRE-BI, Onto-CoM, SeCoGIS, Variability@ER, WISM, Brussels, Belgium, October 31 - November 3, 2011. Proceedings - Troyer, Olga.; Bauzer Medeiros, Claudia; Billen, Roland; Hallot, Pierre; Simitsis, Alkis; Mingroot, Hans.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of workshops, held at the 30th International Conference on Conceptual Modeling, ER 2011, in Brussels, Belgium in October/November 2011. The 31 revised full papers presented together with 9 posters and demonstrations (out of 88 submissions) for the workshops and the 6 papers (out of 11 submissions) for the industrial track were carefully reviewed and selected. The papers are organized in sections on the workshops Web Information Systems Modeling (WISM); Modeling and Reasoning for Business Intelligence (MORE-BI); Software Variability Management (Variability@ER); Ontologies and Conceptual Modeling (Onto.Com); Semantic and Conceptual Issues in GIS (SeCoGIS); and Foundations and Practices of UML (FP-UML).
Electronic reproduction.
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; Software Engineering; Database Management; Electronic books